Endoscopic Effects on Peristaltic Flow of a Nanofluid - Akbar, Noreen Sher; Nadeem, S (Communications in theoretical physics, 2011)
In the present investigation we have studied the peristaltic flow of a nanofluid in an endoscope. The flow is investigated in a wave frame of reference moving with velocity of the wave c. Analytical solutions have been calculated using Homotopy perturbation method （HPM） for temperature and nanoparticle equation while exact solutions have been calculated for velocity and pressure gradient. Numerical integration have been used to obtain the graphical results for pressure rise and frictional forces. The effects of various emerging parameters are investigated for five different peristaltic waves. Streamlines have been plotted at the end of the article.